Thermal and composting degradation of EVA/Thermoplastic starch blends and their nanocomposites. (January 2019) - Sessini, Valentina; Arrieta, Marina P.; Raquez, Jean-Marie; Dubois, Philippe; Kenny, José M.; Peponi, Laura
Abstract: In this work, the thermal degradation and the disintegrability under composting conditions of melt-processed blends based on ethylene-vinyl acetate and thermoplastic starch, EVA/TPS, as well as their nanocomposites, reinforced with natural bentonite, were studied. A special emphasis was first put on the influence of starch on the morphology, thermomechanical properties and hydrophilicity of these blends before composting analysis. In fact, the materials were characterized in terms of morphological, mechanical, thermal and structural properties as well as wettability performance, obtaining information about the immiscibility of the blends and their compatibilization when natural bentonite is used. The thermal stability of starch was increased according with the EVA content in the blend, while the compatibility between both polymeric phases was increased by adding the nanoclays. Consequently, the disintegration under composting condition at laboratory scale level of the obtained materials was conducted and the thermal and chemical-structural properties as well as the surface microstructural changes of recovered samples at different stages of disintegration were studied. Disintegration tests showed that EVA/TPS blends and their nanocomposites presented positive interactions, which delay the disintegration of TPS matrix in compost, thus improving TPS stability. Moreover, blending biodegradable polymers such as TPS with non-biodegradable polymers like EVA leads to the increase of compostable polymer percentage in partially-degradable materials giving a possible solution for the end-life of these materials after their use. Highlights: The thermal, chemical-structural as well as surface microstructural changes of disintegrated sample were studied. Natural bentonite increase the EVA/TPS compatibility delaying the disintegration of TPS matrix in compost. Melt-blending TPS with EVA increase the stability of starch-based materials.